AFRICA AND RECOLONIZATION: DIALECTICS OF MAZRUIAN THEORETICAL STATEMENT - EDO, Uvie Tobore; OSIMERAH, Charles Aleonokhua; EBHODAGHE, Isaac Ighodalo; BOUBAI, Joseph Jackson (EBSU Journal of Social Sciences and Humanities, 2024)
Right from time, theoretical framework constitutes the central curvature of learning fore grounded in structured survey which projects a typical study of history and the present and providing predictive synergy. The paper is anchored on qualitative research, which explores mainly the secondary sources of data with specific reference to relevant journal articles, text books, internet and other archives. Thus, content analysis was utilized to analyze the issues raised in the paper. As unraveled, Africa has been consummated in tripartite imperialism counting from the West multiple incursion to the bipolar Cold War configuration. The third is woven around BRICS emergence in quest of global hegemony resting mainly on Africa, which paradoxically defines Mazruian broad scope of recolonization theory by appraising the ulterior motive of BRICS collage equation and the associated flaws of multi-polarity. Six selected African states constitute the derivate that formally define the total derivation of Africa permanent stasis of elastic imperialism, though spatial, buoyantly justifying the template of recolonization in the Post-New World regime.